Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai Honorer Di Kantor Dinas Pariwisata Kota Medan - Adytia, Muhammad Hanibal (Jurnal sosial dan sains, 2025)
This study aims to analyze the influence of work motivation on the performance of honorary employees in the public sector, with a focus on the Medan City Tourism Office. Honorary employees often work in uncertain conditions and have minimal career security, even though they have an important role in the delivery of public services. The study used a quantitative approach with a cross-sectional survey design, involving 95 randomly selected respondents. Data were collected through a Likert scale questionnaire instrument and analyzed using simple linear regression. The results showed that work motivation had a significant and positive influence on the performance of honorary employees (r = 0.758; p < 0.001), with a contribution to the variance of 57.5%. These findings are in line with the theory of Self-Determination which emphasizes the importance of intrinsic motivation in improving individual performance. This study contributes to the enrichment of public management literature, especially in the context of non-ASN employees who have received less attention. The practical implication of this study is the need for a motivation-based managerial strategy to increase the productivity of honorary employees. In addition, these findings also encourage the importance of formulating policies that are more inclusive of honorary employees in the Indonesian bureaucratic system.